Hashtags for EFL teachers' transformation: an insight into Instagram-mediated reflective practice. Issue 6 (2nd November 2022) - Foltyn, Marzena
ABSTRACT: An important shift in teachers' professional development has emerged since the rising popularity of Instagram. A plethora of educators has adopted this space in pursuit of connection, reflection, new meanings, and entrepreneurial success. English as a Foreign language (EFL) domain is exceptionally fruitful, numerous, and advantageous when compared to other educational settings promoted on this interactive platform. Drawing on seven in-depth interviews, this study uses Pollard's theoretical framework to interpret EFL teachers' perceptions of Instagram as a catalyst for reflective practice. This form of a condensed audit allowed for identifying myriads of benefits such as collaboration, teacherpreneurship, support, inclusiveness, problem-solving, action-orientedness, immediate feedback, and creative mediation. Hopefully, this study may better model teachers' experiences through Instagram-mediated roads of professional development. Clearly, using Instagram for reflective practice turned out to significantly weigh against its limitations in the forms of time consumption and pressure exposure.